Continuous-flow/stopped-flow system incorporating a rotating bioreactor based on a double redox catalytic cycle and electron transfer mediated by osmium complexes. Application in the determination of extremely low levels of glucose - Salinas, Eloy (2002)
The high sensitivity that can be attained by enzymatic amplification via substrate cycling and mediated by the redox polymer [Os(bpy)2ClPyCH2NHpoly( allylamine) (Os-PAA), has been verified by on-line interfacing of a rotating bioreactor and continuous-flow=stopped-flow=continuous-flow processing system. The determination of glucose was possible with a limit of detection of 20 fmol L1 in the processing of as many as 30 samples per hour. Determination at such low levels is of interest in several situations encountered in fermentation biotechnology and clinical chemistry, and for the determination in culture broths; it illustrates the capabilities of the proposed approach. Glucose oxidase and Os-PAA were covalently immobilized on a glassy carbon electrode surface (upper cell body), Glucose dehydrogenase [EC 1.1.1.47] was immobilized on a disk that can be rotated. Substrate cycling was realized via NADH=NADþ that, in conjunction with glucose dehydrogenase, regenerates glucose, the substrate in the glucose oxidase-catalyzed reaction.